Selection of the Parameters in the Synthesis of Ethylenediamine-Folate Using the Plackett Burman Design - Erianti Siska Purnamasari; Linda Septiana; Ari Hardianto; Ukun Mochammad Syukur Soedjanaatmadja; Anni Anggraeni; Husein Hernadi Bahti (Universitas Gadjah Mada, 2022)
This study is concerned with synthesizing ethylenediamine-folate (EDA-Folate), which will then be used as a precursor in synthesizing Gd-PEG-DOTA-Folate, a novel targeted-contrast agent for the diagnosis of cancer, employing the Magnetic Resonance Imaging method. This study aims to determine all the parameters affecting the synthesis of EDA-Folate using the Plackett Burman design. The synthesis method included activation of folic acid using dicyclohexylcarbodiimide and N-Hydroxysuccinimide to result in NHS-Folate, followed by conjugation of ethylenediamine with NHS-Folate to produce EDA-Folate. Analysis of the reaction product confirmed that the reaction product was EDA-Folate. From the resulted data, it can also be concluded that there were four significant parameters (out of the ten parameters studied) in the synthesis of EDA-Folate (with its value presented in the bracket), i.e., time inactivation of NHS-Folate (24 h), stirring rate inactivation of NHS-Folate (300 rpm), the mole of EDA (12 moles), and time of EDA-Folate (12 h). Moreover, the value or desirability of the experimental design was found to be 0.875 (which is < 1.0), meaning that the design will produce optimal conditions and thus the optimal yield of the reaction.